إدارة الصراع التنظيمي و علاقتها بالالتزام لدى لاعبي اندية الـدرجة الاولى بكرة القـدم في اقليم كوردستان العراق - محمود, ا.م.د هونەر صابر; فتاح, م.گۆران مولود (Sulaimani Journal for Humanities, 2023)
The research aims to – Identifying the level of managing organizational conflict among the first-division football players in Kurdistan Region / Iraq. Identifying the level of commitment in first-division football players in Kurdistan Region / Iraq. Identifying the relationship between the management organizational conflict and the commitment of first-division football players in Kurdistan Region of Iraq. The researchers used the descriptive method for its suitability to the current study. The research community included players who participated in first-division league in Kurdistan Region-Iraq for (2021-2022) season and their number was (445) players. (126) players were chosen purposely as the sample of the study. Then, the organizational conflict management and commitment questionnaires were used. After ensuring the scientific conditions in terms of validity and reliability, they were applied to the research sample, in order to reach the achievement of the objectives of the current study, the researchers used the statistical package (SPSS). . The most important conclusions are: 1. The management organizational conflict has a high level from the point of view of the first-division football players in the Kurdistan Region of Iraq. 2. The commitment has a very high level from the point of view of the first-division football players in the Kurdistan Region of Iraq. 3. There is a relationship between organizational conflict management and commitment in first-division football club players in Kurdistan Region- Iraq